Disseminated tuberculosis associated with reactive arthritis of Poncet in an immunocompetent patient - Alves Calado, Juliana de Oliveira [UNESP]; Miola, Anna Carolina [UNESP]; Cavariani Silvares, Maria Regina [UNESP]; Marques, Silvio Alencar [UNESP] (Elsevier B.V., 2020)
Cutaneous tuberculosis is a rare extrapulmonary manifestation of tuberculosis which, like disseminated tuberculosis, commonly occurs in immunocompromised patients. Poncet reactive arthritis is a seronegative arthritis affecting patients with extrapulmonary tuberculosis, which is uncommon even in endemic countries. We report a previously healthy 23-year-old male patient with watery diarrhea associated with erythematous ulcers on the lower limbs and oligoarthritis of the hands. Histopathological examination of the skin showed epithelioid granulomatous process with palisade granulomas and central caseous necrosis. AFB screening by Ziehl-Neelsen staining showed intact bacilli, the culture was positive for Mycobacterium tuberculosis, and colonoscopy revealed multiple shallow ulcers. Disseminated tuberculosis associated with reactive Poncet arthritis was diagnosed, with an improvement of the clinical and skin condition after appropriate treatment. (C) 2020 Sociedade Brasileira de Dermatologia. Published by Elsevier Espana, S.L.U.
Keywords: Arthritis, reactive; Dermatology; Tuberculosis, cutaneous